RESIST-HCV Criteria to Monitor Progression of Low-Risk Esophageal Varices in Patients With Compensated Cirrhosis After HCV Eradication: The SIMPLE Study: SIMPLE: Scoring Index to Monitor Progression of Low-risk Esophageal varices. (21st November 2022) - Calvaruso, Vincenza; Celsa, Ciro; D'Ambrosio, Roberta; Simone, Fabio; Petta, Salvatore; Cacciola, Irene; Enea, Marco; Battaglia, Salvatore; Pandolfo, Alessandra; Licata, Massimo; Degasperi, Elisabetta; Cabibbo, Giuseppe; et al.
Abstract : INTRODUCTION: Noninvasive criteria to predict the progression of low-risk esophageal varices (EV) in patients with compensated hepatitis C virus (HCV) cirrhosis after sustained virological response (SVR) by direct-acting antivirals (DAAs) are lacking. Our aim was to assess the diagnostic performance of Rete Sicilia Selezione Terapia–HCV (RESIST-HCV) criteria for EV progression compared with elastography-based criteria (Baveno VI, Expanded Baveno VI, and Baveno VII-HCV criteria). METHODS: All consecutive patients observed at 3 referral centers with compensated HCV cirrhosis with or without F1 EV who achieved sustained virological response by DAAs were classified at last esophagogastroduodenoscopy (EGDS) as RESIST-HCV low risk (i.e., low probability of high-risk varices [HRV]) if platelets were >120 × 10 9 /L and serum albumin >3.6 g/dL or RESIST-HCV high risk (i.e., high probability of HRV) if platelets were <120 × 10 9 /L or serum albumin <3.6 g/dL. The primary outcome was the progression to HRV. The area under the receiver operating characteristic curve and decision curve analysis of noninvasive criteria were calculated. RESULTS: The cohort consisted of 353 patients in Child-Pugh class A (mean age 67.2 years, 53.8% males). During a mean follow-up of 44.2 months, 34 patients (9.6%, 95% CI 6.7%–13.5%) developed HRV. At the last EGDS, 178 patients (50.4%) were RESIST-low risk, and 175 (49.6%) were RESIST-high risk. RESIST-HCV criteria showed the highest area under the receiver operating characteristic curve (0.70, 95% confidence interval 0.65–0.75), correctly sparing the highest number of EGDS (54.3%), with the lowest false-positive rate (45.7%), compared with elastography-based criteria. Decision curve analysis showed that RESIST-HCV had higher clinical utility than elastography-based criteria. DISCUSSION: Biochemical-based RESIST-HCV criteria are useful to easily predict HRV development after HCV eradication by DAAs in patients with compensated cirrhosis and low-risk EV.